KONTRIBUSI BAHAN ORGANIK NITROGEN DARI SERASAH MANGROVE DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - - Yulma; Gloria Ika Satriani (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2016)
Mangrove leaf litter production is essential matter for organic recycling of productivity and baseline matter for living of mangrove organisms. Mangrove forest in Conservation Area for Mangrove and Bekantan (KKMB) Tarakan is one of Mangrove forest area which is not only for recreation but also ecological function of mangrove living organism’s productivity. The aim of this research was to know the rate of mangrove leaf litter production and Nitrogen organic matter contribution in KKMB Tarakan. This research was conducted from October 2015 to January 2016. The average of mangrove leaf litter productivity were Avicennia alba 3.31 g/m2/day, Rhizopora apiculata 4.65 g/m2/day, Bruguiera parviflora 3.02 g/m2/day and Sonneratia alba 6.20 g/m2/day. The contribution of Nitrogen organic matter from mangrove leaf litter showed that were Avicennia alba 0.0987 g/m2/day, Rhizopora apiculata 0.0755 g/m2/day, Bruguiera parviflora 0.0977 g/m2/day and Sonneratia alba 0.3722 g/m2/day.Key words: litter productivity, litter decomposition, Nitrogen, KKMB